Transforming Plastic Waste into Ecobrick-Based Creative Economy Products in Kebonsari Village, Surabaya : Transformasi Limbah Plastik Menjadi Produk Ekonomi Kreatif Berbasis Ecobrick di Kelurahan Kebonsari, Surabaya - Muhammad Rafly; Khumairoh Hafiz A’inun Naim; Zahrah Aliyah Rachman; Anatasya Rachma Cahyani; Elsa Aulia Adisti; Tri Lathif Mardi Suryanto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The issue of plastic waste in urban areas such as Kebonsari Village requires sustainable solutions that are not only technical but also participatory. This community service activity aims to empower the community through training in the production of ecobricks as a form of transforming plastic waste into creative products with economic value. The method used is participatory-educational, involving residents in every stage of the activity, from education, practical ecobrick making, to the creation of the